Numerical investigation of surface wave generation during immersion of a rigid body into a liquid - Levin, Vladimir Alexeevich; Nadkrinichny, Leonid Vladimirovich (Computational Continuum Mechanics, 2011)
We present a numerical investigation of immersion of a cylindrical rigid body into an unexcited liquid. Generation of water waves and dependence of the parameters of these waves on the body parameters are studied. A shallow water model in a cylindrical coordinate system is applied. A total variation diminishing (TVD) scheme is used on the finite difference C-type grid according to Arakawa’s classification.